PENERAPAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) BERBANTUAN MEDIA POHON BUPIN TERHADAP MINAT BELAJAR SISWA - Keren Asael; Anni Malihatul Hawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Teams Games Tournament (TGT) learning model assisted by Pohon Bupin (Smart Fruit Tree) media on the learning interest of third-grade students at SD Negeri Gedanganak 03. The research method used was a quasi-experiment with a non-equivalent control group design. The research population was all third-grade students, with a sample of class III B as the experimental group receiving the TGT model treatment assisted by Pohon Bupin, and class III A as the control group using the TGT model without media. Data collection instruments included questionnaires, observations, and interviews. Data analysis employed normality tests, homogeneity tests, independent sample t-tests, and simple linear regression with the assistance of SPSS. The results showed: (1) there was a significant difference in learning interest between the experimental and control classes (sig. 0.000 < 0.05); (2) the TGT learning model assisted by Pohon Bupin had a positive effect on students' learning interest (sig. 0.044 < 0.05) with a contribution of 8.2%. Observations also indicated an increase in learning interest in the experimental class with an average of 60% (good) compared to the control class at 57% (good). The conclusion of this study is that the TGT model assisted by Pohon Bupin media is effective in enhancing students' learning interest. It is recommended that teachers implement this model to create more interactive and enjoyable learning experiences.